1996
DOI: 10.1021/ja960293p
|View full text |Cite
|
Sign up to set email alerts
|

π-Stacking as a Control Element in the (2-PhInd)2Zr Elastomeric Polypropylene Catalyst

Abstract: Properties such as the rate of crystallization and degree of crystallinity of polymers formed from vinyl olefins such as propylene can be affected by the tacticity of the material. 1 The tacticity in turn can be controlled by the nature of the active site of the polymerization catalyst. 2 A catalyst active site shape that favors reaction by the same prochiral olefin face will produce isotactic polymer while a catalyst site shape that does not favor one olefin face over the other will produce atactic polymer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 9 publications
1
44
1
1
Order By: Relevance
“…This trend in the [mmmm] values is in accordance with the report by Waymouth et al that not only the catalyst 1 but also its mixed-Cp* derivative also produces polypropylene with a comparable [mmmm] content, while the mixed-Cp complex only gives atactic polypropylene despite its high activity [12a]. The expected stereocontrol by the restricted rotation of the biphenyl substituted ligand might not be effective in the present catalysts system as similarly observed in the case of phenyl or para-tolyl substituted analogue of 3, partially supporting that the indenyl ring fragment is necessary to attain a high [mmmm] value [19]. Therefore, it can be concluded that the counterbalancing effects from both parts of cyclopentadienyl ring fragment and 2-aryl substituent in the Waymouth-type catalyst would be essential in order to produce elastomeric polypropylene.…”
Section: Olefin Polymerizationmentioning
confidence: 65%
See 1 more Smart Citation
“…This trend in the [mmmm] values is in accordance with the report by Waymouth et al that not only the catalyst 1 but also its mixed-Cp* derivative also produces polypropylene with a comparable [mmmm] content, while the mixed-Cp complex only gives atactic polypropylene despite its high activity [12a]. The expected stereocontrol by the restricted rotation of the biphenyl substituted ligand might not be effective in the present catalysts system as similarly observed in the case of phenyl or para-tolyl substituted analogue of 3, partially supporting that the indenyl ring fragment is necessary to attain a high [mmmm] value [19]. Therefore, it can be concluded that the counterbalancing effects from both parts of cyclopentadienyl ring fragment and 2-aryl substituent in the Waymouth-type catalyst would be essential in order to produce elastomeric polypropylene.…”
Section: Olefin Polymerizationmentioning
confidence: 65%
“…b Cp 0 (1); the plane of C(1-5), Ph (1); the plane of C (8)(9)(10)(11)(12)(13), Ph (2); the plane of C (14)(15)(16)(17)(18)(19).…”
Section: Anglesmentioning
confidence: 99%
“…Porphyrin aggregation (1), the conformation of diarylnaphthalenes (2) and phenylacetylene macrocycles (3), and the strength of Kevlar (4) can be attributed, at least in part, to aromatic-aromatic interactions. Aromatic-aromatic interactions have been implicated in catalytic hydroformylation (5), the catalytic formation of elastomeric polypropylene (6), and the asymmetric cis dihydroxylation of olefins (7). The vast majority of medicinal agents contain aromatic substituents and their differential recognition by proteins is likely dominated by aromatic-aromatic interactions (8).…”
mentioning
confidence: 99%
“…Because the huge number of possible conformers and the two degrees of freedom considered, the use of inexpensive molecular mechanics calculations is the only way to obtain something even close to a complete conformational analysis of the systems. This approach has been reported earlier by other groups, 19,20 and we considered the parameter set used by Brinztinger et al appropriate for our problem. Figure 8 and 9 show the molecular mechanics potential energy surfaces for 1 and 2 without consideration of solvent effects.…”
Section: Theoretical Investigationmentioning
confidence: 99%